Pandangan Masyarakat Perkotaan dalam Memilih Lembaga Pendidikan Islam: Studi tentang Parental Choice In Education di SD Plus Rahmat Kota Kediri - Ahsin, Nurul (Didaktika Religia, 2015)
The study aims at investigating how parents select the right school for their children, especially those living in urban areas. The research is field research conducted at SD plus Rahmat Kediri. The method used is descriptive qualitative. The data were collected by interviews, observation and documentation.The results reveal that generally public's views of Islamic educational institutions have experienced dynamics. Islamic schools are now assumed to be superior schools/favorites and become trend for urban communities and communities of upper middle class. The existence of Islamic schools/plus with full day school system is to meet the educational needs of urban communities who are busy and anxious with the religious education of their children.